2005
DOI: 10.1007/s11240-005-4442-1
|View full text |Cite
|
Sign up to set email alerts
|

Trifolium alexandrinum × T. resupinatum – Interspecific Hybrids Developed through Embryo Rescue

Abstract: This is the first report on the development of interspecific hybrids between T. alexandrinum and T. resupinatum, using embryo rescue. T. resupinatum is an important donor species for traits such as resistance to root and stem rot diseases, and tolerance to alkalinity for the potential improvement of T. alexandrinum. T. alexandrinum, as female parent, was crossed with T. resupinatum and embryos were excised 10-12 days after pollination and cultured in vitro on EC3 medium. Of the recovered embryos, 23.08% showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…This corresponds to the results of Isobe et al (2001), who observed different leaf morphologies between BC 4 plants and T. pratense in the same cross combination in comparison with the parental species. The intermediate morphological appearance of interspecific hybrids was also observed in other species combinations, such as T. alexandrinum × T. apertum , T. alexandrinum × T. constantinopolitanum and T. alexandrinum × T. resupinatum (Kaushal et al 2005). A few hybrids of T. alexandrinum × T. apertum also showed better growth than either parent .…”
Section: Discussionsupporting
confidence: 52%
“…This corresponds to the results of Isobe et al (2001), who observed different leaf morphologies between BC 4 plants and T. pratense in the same cross combination in comparison with the parental species. The intermediate morphological appearance of interspecific hybrids was also observed in other species combinations, such as T. alexandrinum × T. apertum , T. alexandrinum × T. constantinopolitanum and T. alexandrinum × T. resupinatum (Kaushal et al 2005). A few hybrids of T. alexandrinum × T. apertum also showed better growth than either parent .…”
Section: Discussionsupporting
confidence: 52%
“…Embryo culture technique has been successfully used to obtain interspecific hybrids in crops such as Trifolium and tomato. This method offers the chance to rescue plantlets from underdeveloped embryos by culturing on a suitably nutritional medium (Evans, 1962;Katznelson, 1971;Segeren et al, 1993;Kaushal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Williams (1978) noted that only 30 embryos from many hundred pollinated flowers were large enough for dissection and only 6 showed any growth in culture. In other research on hybridization between Trifolium alexandrinum and T. resupinatum, out of 556 crossing attempts, a total of 26 ovules were recovered (Malaviya et al, 2004a;Kaushal et al, 2005). In our study, after nearly 4-5 months of culturing in vitro, the remaining 53 were transferred to vermiculite.…”
Section: Resultsmentioning
confidence: 50%